A produção e os acessos de conteúdos jornalísticos de interesse público por meio da ferramenta QR Code: um estudo de caso do jornal O Popular - Rigueiral, Jaísa Gleice Rodrigues dos Santos Picazo (2024)
Public interest in Journalism is both part of professional culture and a deontological and theoretical value in studies on Journalism. This dissertation aims to understand the presence of public interest in the content of the news presented in the TV commercial “Leia Agora em O Popular”, as well as access through the QR Code. This quick response code is a strategy implemented with the aim of gaining readers for the printed and digital versions of the newspaper “O Popular”, founded in Goiás in 1938, and with a wide reach in the state and the Central-West region. This is a case study that combines qualitative and quantitative approaches. Theoretically, the relationship between journalism of business nature and public interest as a component of the social discourse that legitimizes Journalism is discussed, with a view to understanding this new commercial tool. It is also investigated whether the materials of public interest to be made available on the QR Code are present in the selection by the editors and reporters of “O Popular” and whether they are accessed by readers. It is concluded that, although the QR Code is an insignificant strategy for converting readers into subscribers, content of public interest is valued by the newspaper O Popular and also captures the interest of readers.